ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENETAPAN AUDIT FEES (Studi Empirik Pada Perusahaan Manufaktur di BEI) - Raymond Immanuel; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2014)
This study aims to examine the factors that may affect the determination of the external audit fees on companies listed in Indonesia Stock Exchange (IDX) in the year 2011-2013. Factors that affect the determination of the external audit fees are the type of ownership of the company is divided into private and state-owned, firm size measured by total assets of the company, the existence of a subsidiary, KAP size divided into non-big four big four, and earnings management measured by discretionary accruals Modified Jones (2010).By using purposive sampling method samples obtained financial reports at least 138 companies. To analyze the effect of the type of ownership of the company, size of company, the existence of a subsidiary, the firm size, and earnings management, used multiple linear regression analysis. The results showed that the size of the company, a subsidiary, and the size of the firm have a significant effect in the determination of audit fees. While the variable of type of ownership and earnings management company does not have a significant effect on audit fees.